A Polícia Militar do Estado de São Paulo e as novas competências da Justiça Militar Estadual (LEI n.º 13.491/17) - Tarelov, João Fábio (2021)
The State Military Justice is responsible for processing and judging military crimes committed by the state military, which are composed of the military police forces of the states and the Federal District, defined in the Military Penal Code and observing the procedures provided in the Code of Military Criminal Procedure. The military police are some of the security institutions responsible for public security, exercised to preserve public order and the safety of people and property, as determined by the 1988 Federal Constitution. The military police forces are responsible for ostensible police and the preservation of public order; the military firemen are also responsible for civil defense activities. The State Military Justice has an extremely important role, as a member of the Judiciary, which guarantees to society that the Fundamentals of the Federative Republic of Brazil will be rigorously fulfilled by the military police in the exercise of their police powers as determined by law. With the enactment of Law 13.491/17, there was an innovation in the Brazilian legal system, when it expanded the competencies of the State Military Justice, an organ of the Judiciary Power, as well as expanded the competencies for the military police, while exercising the attributions as military judicial police, to assist in the investigation and in the formation of the military police investigation, to subsidize the Military Justice in the evidentiary set for the proposition of the military criminal action, in cases of the commission of military criminal infractions committed by the state military, guaranteeing for society that any violations will be duly processed and judged in an impartial and independent way, because it is an efficient justice. The military police officers that make up the Military Police of the State of São Paulo are jurisdictionally protected by the Military Justice of the State of São Paulo, represented by the Military Court of Justice in the state, which is one of the three existing in the country. They form the second instance in these states of Brazil, in the other states the military second instance is assigned by the Courts of Justice in the states. The existence of the Military Courts of Justice is a constitutional prevision, based on the principle of efficiency, due to the specialty that these courts must possess in order to apply the laws concomitantly, observing the basic principles of the military, which are hierarchy and discipline, to guarantee that the military institutions are not compromised and that their commanders always act within the law, while any violation committed, in the commission of military crimes by the state military, will be up to the State Military Justice its effective and efficient maintenance, so that society can live together peacefully and harmoniously believing that everyone is reached by the law.